The misuse of drugs in Malaysia: past and present - Kamarudin, Abdul Rani (Agensi Antidadah Kebangsaan Kementerian Dalam Negeri, 2007)
This paper gives a historical insight on how drugs first came to be commercially introduced into South East Asia including Malaysia, and the early measures taken to control and regulate their usage. It also explains the origin of their usage in Malaysia up to a stage when it became cancerous to the country, requiring the government to take drastic measures to combat them. Accordingly, this paper primarily discusses the Dangerous Drugs Act 1952 which is the foremost statute on the dangerous drugs laws of Malaysia, and the Malaysian government's stance or policy over the misuse of narcotic drugs.